Yearbook of Private International Law. (Yearbook of Privat International Law ;, 2014)
Private International Law on the Move In line with ist predecessors, Volume XV (2013/2014) of the Yearbook of Private International Law offers a comprehensive insight into the contemporary trends of private international law in terms of both theoretical thinking and practical achievements. The volume includes two contributions from prominent scholars on freedom of movement of public documents and records within the EU, a whole section on Brussels Ibis Regulation, a dozen national reports on recognition and enforcement of foreign judgments*outside the EU from Turkey to Australia, from Russian Federation to Egypt, from South Korea to Commonwealth Africa as well as an overview of the new codification in Albania. Two essays on internal conflict of laws and on the challenges posed by cross-border coordination in insolvency matters complete this valuable collection.